An evaluation of engineering periodical collections in Metro Manila - Manalo, Elenita R. (1998)
The objectives of this study are to evaluate the engineering periodical collections of 23 engineering college/schools in relation to up-to-dateness, growth rate, strengths and weaknesses perceived by faculty members and engineering students.